Shiny Dashboard aplikace pro regresní analýzu - Osadcha, Tetiana (2024)
The aim of this thesis is to present the Shiny Dashboard application which was written as a part of this work. The application allows user to perform the regression analysis on a given dataset. The first part of the thesis describes regression types which are implemented in the application. The practical part describes the results obtained from the application using two different datasets. It shows how the application can be used to analyse the data and provides a guideline for a user to do their own calculation.